2008
DOI: 10.3923/pjbs.2008.1625.1629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Locally Produced Blood Meal on Performance, Carcass Traits and Nitrogen Retention of Broiler Chickens

Abstract: The study was designed as a 2 x 5 factorial arrangement with main effects of feeding blood meal as a replacement of 0, 25, 50, 75 or 100% of dietary fish meal and the duration of this substitution at 1-42 or 21-42 days of age. One thousand 1 day old male Cobb 500 broiler chicks assigned randomly to each of 40 floor pens (25 birds/pen) and were fed five isonitrogenous and isocaloric feeds formulated to contain 20.38 and 17% crude protein and 2900 and 3000 kcal kg(-1) metabolizable for starter and grower periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The inclusion of 5% blood meal showed lowest final body weight. This result was in disagreement with previous studies where broiler diets supplemented with MBM (2, 3.5 and 5%), feather meal (33, 67 and 100%) and blood meal (50 and 100%) instead of fishmeal were not significant effect on final body weight (Bozkurt et al, 2004;Hasni et al, 2014;Seifdavati et al, 2008). Moreover, Frempong et al (2019) found that replacing fish meal with poultry by-products meal resulted in higher body weights.…”
Section: Final Body Weight and Cumulative Growth Performancementioning
confidence: 58%
See 1 more Smart Citation
“…The inclusion of 5% blood meal showed lowest final body weight. This result was in disagreement with previous studies where broiler diets supplemented with MBM (2, 3.5 and 5%), feather meal (33, 67 and 100%) and blood meal (50 and 100%) instead of fishmeal were not significant effect on final body weight (Bozkurt et al, 2004;Hasni et al, 2014;Seifdavati et al, 2008). Moreover, Frempong et al (2019) found that replacing fish meal with poultry by-products meal resulted in higher body weights.…”
Section: Final Body Weight and Cumulative Growth Performancementioning
confidence: 58%
“…Blood meal (BM) is a by-product of the slaughtering industry and is used as a protein source in the diets of non-ruminants and ruminants (Seifdavati et al, 2008). Blood meal is a dark chocolate-coloured powder with characteristics smell.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the experimental period, four birds from each treatment were randomly selected, fasted overnight, and sacrificed for carcass analysis. All carcass traits and relative organ weights were expressed as a percentage of the live weights (Seifdavati et al, 2008).…”
Section: Carcass Traits and Relative Organ Weightsmentioning
confidence: 99%
“…Beside of low cost production, the health status of animals with high growth performance is also important in the choice of feed supplementation. Feed supplementation with high-quality protein has been used chiefly to improve the growth performance and immune system in animals (Fisher, 1998;Seifdavati et al, 2008;Sklan & Noy, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation